THE COMMANDER'S RESPONSIBILITY FOR WAR CRIMES: THE NECESSITY FOR INDONESIA TO ADHERE TO THE ROME STATUTE - Rifqi, Muhammad Ariq; Listriani, Sophia (Student Journal of International Law, 2025)
Commanders responsibility, as recognized in international law, holds military commander responsible for war crimes perpetrated by their subordinates if they fail to prevent or punish such actions. However, in Indonesias legal framework, it is insufficient due to the countrys inability to adhere to the Rome Statute. Indonesian Law No. 26 of 2000 on the Ad Hoc Human Rights Court is indeed regulating the matter of commanders responsibility, but it lacks the provisions for war crimes, which may cause serious risk of hindering the prosecution of war crimes perpetrators. The law also contains significant linguistic flaws on the commanders responsibility provisions, as obtained through comparison with the standards provided in the Rome Statute. The flaws are evident in Article 42(1), where the original wording of the Rome Statute is changed, therefore weakening mandatory responsibility and allowing ambiguous interpretations of the law. This study aims to contribute to the scholarship by analyzing how these legal gaps may prevent responsibility for war crimes. Utilizing normative legal research methodology with library-based and comparative approach, this study analyzes both international and Indonesias national legal instruments, including the Rome Statute, the 1949 Geneva Conventions, and Law No. 26 of 2000, alongside secondary sources such as academic literatures and historical precedents from tribunals such as Nuremberg. The findings reveal that Indonesias failure to incorporate war crimes provisions prevent justice in unresolved cases, such as the Timor-Leste Case, and undermines its compliance with International Humanitarian Law. Furthermore, this study proposes legal reform, with a possible ratification of the Rome Statute, as crucial measures to strengthen Indonesias responsibility mechanisms.